Relationship Between Occupational Stress Dimensions and Sickness Absence Among a Gas Company Employees - Rezvan Zare; Alireza Choobineh; Sareh Keshavarzi (Shiraz University of Medical Sciences, 2016)
Background: Working conditions have considerably changed and exposure to psychosocial risk factors, particularly occupational stress, has recently had an increasing trend. Studies have shown that sickness absence was the worst outcome of occupational stress. The present study aimed to assess the relationship between dimensions of occupational stress and sickness absence in a gas company in Boushehr, Iran. Methods: This cross-sectional study was conducted on 400 employees of a gas company, Boushehr, Iran who were selected through random sampling. Osipow occupational stress questionnaire was used to determine the participants' stress levels. Then, the data were analyzed using descriptive statistics and Kruskal-Wallis test. Results: The participants' mean of sickness absence was 2.164.57± days per year. Besides, 1.5%, 32.5%, 36.3%, and 29.8% of the participants had low, low to moderate, moderate to severe, and severe occupational stress, respectively. Additionally, the mean of total stress was moderate to severe among the study participants. This was also the case concerning the stress dimensions. The results revealed a significant relationship between the number of sickness absences and dimensions of occupational stress, including workload, role insufficiency, role conflict, responsibility, physical environment, and total stress (P=0.0001). Conclusion: The majority of the employees had high levels of occupational stress. Besides, a significant association was observed between the dimensions of occupational stress and sickness absence. Accordingly, to decrease the number of sickness absence, we should take measures to reduce occupational stress.